Workability and compressive strength of self-compacting geopolymer concrete exposed to elevated temperature - Chithambaram, S. Jeeva; Kumar, Sanjay; Prasad, M.M. (Journal of Structural Engineering, 2024)
This paper reports the workability and compressive strength behaviour of geopolymer concrete using fly ash as thesource material for the first part of the study. Also, partial replacement of fly ash by Ground Granulated Blast FurnaceSlag (GGBFS) with 10%, 20%, 30% and 40% were investigated with varying NaOH concentrations of 8M, 10M, 12Mand 14M. The workability of geopolymer concrete and its hardened properties were studied using different tests forflowability as per EFNARC specifications and Indian standard specifications, respectively. For the second part, the28 days matured specimens were subjected to elevated temperatures from 200°C to 1000°C with an interval of every200°C and their corresponding weight loss and deferred strength were studied. The test results indicated that thecompressive strength of specimens under normal air curing increases with addition of GGBFS as partial replacementof fly ash up to 30% beyond which the strength decreases marginally. Also, the compressive strength values increasewith increase in NaOH concentration up to 12M. Further, the increase in NaOH concentration to 14M shows adecrease in the compressive strength of Self-Compacting Geopolymer Concrete (SCGC) irrespective of the addition ofGGBFS dosage. Tests on SCGC subjected to elevated temperatures showed that for all cases, the compressive strengthvalue decreases gradually with an increase in temperature up to 400°C beyond which a steep decrease in compressivestrength was found until 1000°C. The effect of elevated temperature on the compressive strength of SCGC had a directrelation with that of the weight loss with increase in temperature. The SCGC specimens prepared with 12M NaOHconcentration and with 30% GGBFS as partial replacement of fly ash yielded the maximum strength with the differentcombinations experimented.